Implementation of Physical Education Learning Based on Local Wisdom in the Form of Traditional Games in Balangan Regency - Aldiyanor, Muhammad; Rakhman, Arie; Rahmadi, Rahmadi (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to analyze the implementation of local wisdom-based Physical Education learning through traditional games in Elementary Schools in three sub-districts in Balangan Regency. The study used a quantitative approach with a descriptive method. Data were collected through structured observations in six accredited elementary schools selected by purposive sampling. The results showed that traditional games Baasinan and Balogo were the types most widely used in learning. These games support the development of students' motor skills such as coordination, agility, strength, and balance. The integration of traditional games in core learning has been shown to increase students' motivation, participation, and understanding of the concept of movement. Despite the limited number of teachers and high workload, teachers are still able to carry out learning systematically, including in the evaluation aspect.